865. NEPENTHES DUBIA: Nepenthaceae. (26th July 2017) - Cheek, Martin; Jebb, Matthew; Mansur, Muhammad; Beattie, James
Abstract : The history, taxonomic placement, relationships, mode of trapping and cultivation of Nepenthes dubia Danser, an epiphytic fly‐eater from the cloud forests of the Bukit Barisan range of the west coast of Sumatra, are discussed. This is one of the eight species of Sect. Montanae Danser with 'egg‐cup' like pitchers. A key is provided to the eight species and they are formally named as N epenthes Sect. M ontanae subsect. Poculae‐ovis .